Mass transfer analyses of reactive boundary schemes for lattice Boltzmann method with staircase approximation - Zi-Xiang Tong; Ming-Jia Li; Yanxia Du; Xianxu Yuan (Advances in Aerodynamics, 2024)
Abstract Lattice Boltzmann (LB) methods with reactive boundary conditions are widely used in pore-scale simulations of dissolution and ablation processes. The staircase approximation of curved boundary is often employed because of its simplicity in handling solid structure changes. In this work, the mass transfer of two typical LB reactive boundary schemes are analyzed for the staircase boundary. The Type I boundary scheme is based on relations of local distribution functions and a wet-node boundary mesh. The Type II boundary scheme adopts the half-way bounce-back scheme. Boundary concentrations are determined by finite difference, and a link-wise boundary mesh is used. The analyses demonstrate that for straight boundaries, both the boundary schemes have accurate mass transfer rates, which means the mass transfer calculated by exchanges of distribution functions is the same as that calculated by reaction rates. For curved boundaries with staircase approximation, including interfacial normal directions in the Type I boundary scheme can provide accurate mass transfer for inclined straight boundaries. However, if the staircase boundary geometry is used directly without normal directions, the reaction rate will be overestimated. One-dimensional and two-dimensional reaction-diffusion processes with dissolution are simulated to validate the analyses. Both the boundary schemes work well for one-dimensional simulations. For two-dimensional simulations, the Type II boundary scheme significantly overestimates the reaction rate, and stronger artificial anisotropic effects are observed. The Type I boundary scheme with normal directions has better performance, but error still exists.